Serpentine parent materials lead to the formation of atypical hydric soils. Issue 4 (23rd July 2020) - Vaughan, Karen L.; DeMoss, Jason; Cullum‐Muyres, Taylor; Diaz, Ariel
Abstract: Hydrologically isolated wetlands offer critical ecosystem services including water filtration and storage, carbon sequestration, and wildlife habitat, among many others. Geomorphic features formed via landslides, termed slump blocks, along the central coast of California can create the ideal, lower angle conditions for wetland hydrology to persist, followed by hydrophytic vegetation and hydric soils. Areas susceptible to the formation of slump block wetlands are those along steep slopes underlain by metamorphosed ultramafic (serpentine) colluvial and residual parent materials due to their propensity to slip along fracture planes. The soils that form in these settings do not exhibit traditional redoximorphic features near the surface that are necessary to identify wetland soils via field observation of morphological features. The objective of this study is to examine the morphology of hydromorphic soils forming in serpentine colluvium and residuum and determine wetland status by employing a combination of biogeochemical, hydrological, and vegetative assessments. These serpentinite‐derived soils forming on slump block geomorphic surfaces meet the technical standard of hydric soils using Indicator of Reduction in Soil tubes as a proxy, despite the lack of traditional observable redoximorphic features. In addition, both wetland hydrology and hydrophytic vegetation communities were documented, therefore meeting the three requirements of wetlands. Ultimately, the importance lies in properly identifying and delineating ecosystems in need of conservation and as such, we propose an alternate field indicator for use in serpentine soils forming in landslide‐susceptible terrain.